Clinical Characteristics, Diagnosis, Treatment, and Mortality Rate of TB/COVID-19 Coinfectetd Patients: A Systematic Review - Koupaei, Maryam; Naimi, Adel; Moafi, Narges; Mohammadi, Paria; Tabatabaei, Faezeh Sadat; Ghazizadeh, Soroosh; Heidary, Mohsen; Khoshnood, Saeed (Frontiers in Medicine, 2021)
Introduction: Novel coronavirus (Covid-19) and tuberculosis (TB) are the newest and oldest global threats, respectively. In the Covid-19 era, due to the health system's focus on the Covid-19 epidemic, the national TB control program received less attention, leading to a worsening of the global TB epidemic. In this study, we will review the characteristics of TB patients superinfected with COVID-19. Material and methods: Using Scopus, PubMed/Medline, Embase, and Web of Science data bases, a systematic search was performed. Case reports and case series on TB/ Covid-19 coinfection published 1 Jan 2019 to 24 Feb 2021 were collected. There were not any limitation regarding publication language. Results: Eleven case series and twenty case reports were identified from 18 countries, with the majority of the India (N=6) and China (N=4). Overall, 146 patients (114 men and 32 women) coinfected with TB and COVID-19 enrolled. Smoking (15.07%), diabetes (14.38%), hypertension (8.90%), and alcoholism (7.53%) were the most frequent comorbidities among these patients. The COVID-19 patients with TB mainly suffered fever (78.767%), cough (63.698%), dyspnea (18.493%), and respiratory distress (22.602%). Hydroxychloroquine (63.953%), lopinavir/ritonavir (39.534%) and azithromycin (26.744%) were the most common treatments for them. Conclusion: Patients with TB are more likely to get Covid-19 infection. Because the symptoms of both diseases are similar, it is difficult to diagnose them, and sometimes the diagnosis of TB occurs later, which causes the progression and severity of the disease. Therefore, patients with TB should be screened regularly, even during the Covid-19 epidemic, to prevent the spread of the disease.